Fibromuscular dysplasia and aortic dissection - Puppo, Antonio M; Caro, Manuel Fernández; Sastre, Sara Martín; Gómez, Francisco T; Sánchez, Jose Mariá López (Journal of Cardiology and Cardiovascular Medicine, 2022)
Fibromuscular dysplasia is a rare, non-atherosclerotic, non-inflammatory vascular disease that typically affects women between the ages of 20 and 60 years. Although any artery can be affected fibromuscular dysplasia most commonly affects the renal and carotid arteries. Fibromuscular dysplasia of the renal arteries usually presents with hypertension, while carotid or vertebral artery disease causes transient ischemic attacks, strokes, or dissection. Aortic dissection is rare. We present the clinical case of a patient with fibromuscular dysplasia with type B aortic dissection.